Numerical solution of system of two Nonlinear Volterra Integral equations - Maturi, Dalal Adnan (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
In this paper, using the implicit trapezoidal rule in conjunction with Newton’s method to solve nonlinear system.We have used a Maple 17 program to solve the System of two nonlinear Volterra integral equations. Finally, several illustrative examples are presented to show the effectiveness and accuracy of this method.